Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/life12050682
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cannabis on Multiple Sclerosis-Related Symptoms

Abstract: Multiple sclerosis (MS) is known as an autoimmune disease that damages the neurons in the central nervous system. MS is characterized by its most common symptoms of spasticity, muscle spasms, neuropathic pain, tremors, bladder dysfunction, dysarthria, and some intellectual problems, including memory disturbances. Several clinical studies have been conducted to investigate the effects of cannabis on the relief of these symptoms in MS patients. The efficacy of Cannabis sativa (C. Sativa) in the management of MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…For the indication muscle spasm, these results were comparable. A recent review supported Sativex’s ® (an oral spray of balanced Δ-9-THC and CBD) effectiveness on multiple sclerosis pain and spasticity, with improvements in sleep and QoL [ 38 ]. Another prospective study found 70.5% of patients reported a ≥20% improvement in symptoms after one month [ 39 ], which agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For the indication muscle spasm, these results were comparable. A recent review supported Sativex’s ® (an oral spray of balanced Δ-9-THC and CBD) effectiveness on multiple sclerosis pain and spasticity, with improvements in sleep and QoL [ 38 ]. Another prospective study found 70.5% of patients reported a ≥20% improvement in symptoms after one month [ 39 ], which agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Pain experienced by MS patients can be divided into multiple categories, such as continuous central neuropathic pain, intermittent central neuropathic pain, musculoskeletal pain, and mixed neuropathic and non-neuropathic pain. 167 Treatment should ideally be targeted towards the specific modality experienced by the patients. Indirect or secondary causes of pain such as spasticity, alteration of gait mechanics, or fatigue should be managed separately (and are addressed in other sections of the paper).…”
Section: Painmentioning
confidence: 99%
“…Many reports demonstrated the beneficial effects of cannabinoids in multiple sclerosis based on their immunosuppressive, neuroprotective, remyelinating and analgesic effects [ 261 , 262 , 263 ]. For example, in Theiler’s virus infection of the CNS, which induces an immune-mediated demyelinating disease resembling multiple sclerosis, synthetic CBR agonists WIN 55,212–2 (nonselective CB1/CB2 agonist), ACEA (selectivity over CB1R), and JWH-015 (selectivity over CB2R) improved motor functions, reduced microglial activation and number of CD4+ infiltrating T-cells in the spinal cord, and promoted remyelination in infected animals, clearly suggesting the therapeutic potential of targeting ECS in multiple sclerosis [ 264 ].…”
Section: Cb2r In Multiple Sclerosismentioning
confidence: 99%